2022
DOI: 10.1051/smdo/2022014
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Young's modulus of woven composite material made by Raphia vinifiera fiber/epoxy

Abstract: This work focuses on the optimal design of the woven fabrics made from Raphia vinifiera, fiber, and their contribution as reinforcing element in the epoxy matrix. The work is done alternately experimentally and theoretically. The woven made of canvas, twill and satin armor are characterized in traction according to the ISO13934-1 standard [1]. A predictive mathematical model of Young's modulus of the woven with the greatest rigidity is established. The woven reinforcement composite made is characterized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…As the demand for bio-composites with plant fibre reinforcements is increasing [7], the development of a predictive model to characterise (mechanical, physical) a material without having to resort to experimentation can save time and costs by making composites more accessible [11]. Among the methods for predicting the characteristics of short fibres composites is mathematical homogenisation [12], which is achieved by empirical models such as the law of mixtures [13], Halpin-Tsai (HT) [14], Cox-Krenkel [15], or Kelly and Tyson models [16], which allow the analytical prediction of the mechanical behaviour of composites, saving considerable time in the process of popularising bio-composites [17]. Among the methods of all the statistical analysis methods, only the weibull method [18], offers the particularity of providing information on the severity of the factors inducing the failure of the composite while predicting its mechanical behaviour [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the demand for bio-composites with plant fibre reinforcements is increasing [7], the development of a predictive model to characterise (mechanical, physical) a material without having to resort to experimentation can save time and costs by making composites more accessible [11]. Among the methods for predicting the characteristics of short fibres composites is mathematical homogenisation [12], which is achieved by empirical models such as the law of mixtures [13], Halpin-Tsai (HT) [14], Cox-Krenkel [15], or Kelly and Tyson models [16], which allow the analytical prediction of the mechanical behaviour of composites, saving considerable time in the process of popularising bio-composites [17]. Among the methods of all the statistical analysis methods, only the weibull method [18], offers the particularity of providing information on the severity of the factors inducing the failure of the composite while predicting its mechanical behaviour [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out on Raphia vinifera fibres (RVFs) from the stem to determine its mechanical and physical properties for potential application in composites [24]. This work has shown that RVF can be used for the development of bio-composites [17] and the production of cellulose [25]. Work on the development of composites reinforced with RVF from sheets has shown that the addition of short, random fibres reduces the mechanical properties (modulus and strength) of the polyester matrix [26].…”
Section: Introductionmentioning
confidence: 99%
“…This work begins with the modeling and simulation of heat transfer by conduction through the composite raffia vinifiera fiber, epoxy resin by the finite element method in Abaqus software. Then by the realization and the physical and thermal characterization of the composite since a mechanical characterization of the material was already made (Djoumessi et al, 2022). Finally, by a comparative study between the theoretical results and those experimental; as well as those of the literature.…”
Section: Introductionmentioning
confidence: 99%